2018
DOI: 10.1177/0273475318786026
|View full text |Cite
|
Sign up to set email alerts
|

Intercollegiate Social Media Education Ecosystem

Abstract: The popularity of social media among students and practitioners has encouraged marketing educators to find ways to incorporate social media into their classrooms. We offer results from an intercollegiate collaboration that provides an innovative learning environment through a social media education ecosystem. Participating students discuss current marketing topics with peers, marketing practitioners, and faculty to reinforce course concepts, improve learning perceptions, and increase professional communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Some studies have demonstrated that social networks improve the individual's consumption of learning services and optimize learning outcomes. For example, Abney et al (2019) emphasised the importance of tools such as Twitter for stimulating debate between students and teachers in marketing learning. Kurthakoti et al (2013) verified that using social networks increases the performance of work teams, while McCorkle and McCorkle (2012) concluded that LinkedIn helps individuals to acquire transversal skills, such as social communication and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that social networks improve the individual's consumption of learning services and optimize learning outcomes. For example, Abney et al (2019) emphasised the importance of tools such as Twitter for stimulating debate between students and teachers in marketing learning. Kurthakoti et al (2013) verified that using social networks increases the performance of work teams, while McCorkle and McCorkle (2012) concluded that LinkedIn helps individuals to acquire transversal skills, such as social communication and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Facebook and Twitter are among the most intensively investigated social media platforms for their credibility in education and various aspects of social media were examined in this research, focusing on such platforms because of their widespread and ever-increasing use across all age groups around the world, in particular among the younger generation. Additionally, these platforms were also incorporated into formal classrooms with the efforts of educators primarily aiming for student engagement (Abney, Cook, Fox, & Stevens, 2018). Being the most popular social media platform ever (Smith & Anderson, 2018), Facebook is reported to have features contributing to communication skills with peers and school or faculty members, participation, collaboration, peer support, commitment in educational activities (Tiryakioglu & Erzurum, 2011).…”
Section: Facebook and Twittermentioning
confidence: 99%
“…Combining marketing simulations with case analyses in the marketing capstone course allows students to make and implement decisions (Blackford & Shi, 2015). Other forms of technology mentioned include blogs (Ferguson, Makarem, & Jones, 2016), third-party certifications (Kim, Hettche, & Spiller, 2019), the creative use of social media (Abney, Cook, Fox, & Stevens, 2018), and marketing analytics projects (Ferrell & Ferrell, 2020;Key, Czaplewski, & Ferguson, 2019;Liu & Burns, 2018;Liu & Levin, 2018).…”
Section: Engaged Learning and Technologymentioning
confidence: 99%